ASPEK KEMUKJIZATAN AL-QUR’AN TENTANG KESEHATAN - Yogi Imam Perdana (Universitas Islam Negeri Imam Bonjol Padang, 2016)
This article studies the al-Qur’an’s miracle about healthy. Method used in this writing descriptive qualitative. Result of study indicate that al-Qur’an has the spesial guidance about healthy, among of them how to keep the healthy, how to improve the healthy, consume the right food, how to treat the illness and the balance between physical and spiritualneeds.